Photobiomodulation Therapy In Enhancing Soft Tissue Healing For Aesthetic Procedures: A Systematic Review - Asiyah Syaharuddin (CV. AFDIFAL MAJU BERKAH, 2026)
Photobiomodulation Therapy (PBMT) has emerged as a promising non‑invasive adjunct to accelerate soft tissue healing and improve aesthetic outcomes in cosmetic dental procedures. However, clinical evidence remains heterogeneous, with inconsistent laser parameters and limited comparative data on aesthetic endpoints. This study aimed to evaluate the clinical effectiveness of PBMT in enhancing soft tissue healing and aesthetic outcomes relative to conventional methods in aesthetic dentistry. It employed a systematic review design following the PRISMA 2020 guidelines, using a PICOS framework to search SpringerLink, ScienceDirect, and PubMed for English‑language articles (2020–2025) involving human or animal studies on PBMT and oral soft tissue aesthetics. Seven studies met the inclusion criteria and were analyzed using narrative synthesis without meta‑analysis due to high heterogeneity. Inclusion criteria specified open‑access full‑text articles on gingival contouring, implant surgery, soft tissue grafting, and related procedures, with outcome data on epithelialization, angiogenesis, pain, patient satisfaction, color, and texture. Quality assessment was performed using the Joanna Briggs Institute (JBI) Critical Appraisal Tools. The results show that PBMT consistently improves epithelialization, reduces postoperative pain, enhances tissue color and texture, and increases patient satisfaction, while minimizing hypertrophic scar risk. In conclusion, PBMT accelerates soft tissue healing and aesthetic recovery, though parameter standardization is needed.